As delegadas de polícia de São Paulo: profissão e gênero - Silveira, Maria Natália Barboza da (2009)
The central objective of the research was to study the presence of women in legal careers working as a district chief of police, which is traditionally a male profession. For the development of this research were used two sources of analysis. The objective of the first was to examine women's participation of the profession through the statistics on this professional group. The objective of the second was to evaluate the Women s Police Stations to enable people to verify if the market reserve established by this institution contributed to a process of subordination of these professionals in comparison to their peers. The study made it possible to find out that, on one hand, the inauguration of the DDM's (Delegacias de Defesa da Mulher) channeled more women to work in these stations, on the other, contributed to an "imprisonment" of their career. This is because, for many chiefs of police, working in a DDM is considered an obstacle for the career. We also examined the social representations that the DDM developed at the corporation's police and within the profession of delegate of police, and what has changed in the structure and image of those police stations for the police profession. The study was conducted in São Paulo, where police districts were studied and DDM s. The study was conducted from 2007 until 2009. As a research methodology, interviews were done with chiefs of police from DDM s and police districts in order to establish a comparison between these organs. Altogether 12 interviews were conducted, and with 9 women and 3 with men.